Outsourcing, public Input provision and policy cooperation - Thomas Aronsson; Erkki Koskela (Center for Economic Studies and ifo Institute (CESifo), 2009)
This paper concerns public input provision as an instrument for redistribution under international outsourcing by using a model-economy comprising two countries, North and South, where firms in the North may outsource part of their low-skilled labor intensive production to the South. We consider two interrelated issues: (i) the incentives for each country to modify the provision of public input goods in response to international outsourcing, and (ii) whether international outsourcing justifies policy cooperation. If the public input good is substitutable for (complementary with) outsourcing in terms of the production function faced by northern firms, then outsourcing contributes to increase (decrease) the public input provision in the North. For the South, the optimal policy response depends on the level of outsourcing. We also show how policy cooperation with respect to public input provision can be designed to increase the overall social welfare.
Keywords: H21; H25; J31; J62; 330; outsourcing; redistribution; public input goods; asymmetric information